2020
DOI: 10.1177/0961203320935977
|View full text |Cite
|
Sign up to set email alerts
|

Physician–patient interaction and medication adherence in lupus nephritis

Abstract: Objective The quality of physician–patient interaction can have a significant impact on medication adherence. Little is known about this relationship in patients with lupus nephritis. Methods A cross-sectional, quantitative study. Data collected included demographics, current medication, systemic lupus erythematosus disease activity index, medication adherence, beliefs about medicines, shared decision-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…6 A single-center questionnaire study of patients with SLE nephritis in the United Kingdom noted that better patient–doctor relationships predicted good medication adherence; conversely, lower trust was associated with greater risk of anxiety and depression. 9 Patient communication has also been linked to morbidity, as shown in a study by Ward et al describing a lower rate of permanent organ damage in patients with SLE who asked more questions, were more assertive, and who expressed more concern during their visits. 10 Communication and provider trust is especially important for patients with cSLE who are transitioning between medical teams.…”
Section: Discussionmentioning
confidence: 99%
“…6 A single-center questionnaire study of patients with SLE nephritis in the United Kingdom noted that better patient–doctor relationships predicted good medication adherence; conversely, lower trust was associated with greater risk of anxiety and depression. 9 Patient communication has also been linked to morbidity, as shown in a study by Ward et al describing a lower rate of permanent organ damage in patients with SLE who asked more questions, were more assertive, and who expressed more concern during their visits. 10 Communication and provider trust is especially important for patients with cSLE who are transitioning between medical teams.…”
Section: Discussionmentioning
confidence: 99%
“…[9] A study in the UK involving ethnically diverse patients with SLE indicated an association between trust in one's physician and medication adherence; however, the association might have been confounded by economic status, basic health literacy, and beliefs regarding medications. [10] Furthermore, both studies did not consider the impact of physician-patient racial mismatches. [3] Meanwhile, this study provides a more robust finding because it demonstrated the association between trust in one's physician and medication adherence after adjusting for more confounding factors among patients who comprised largely of a single ethnic group matched to their physicians.…”
Section: Discussionmentioning
confidence: 99%
“…[9, 10] Moreover, the effects of a physician−patient racial mismatch on distrust have not been considered. [3, 9, 10] Separately, having hope is an important coping strategy and a useful means of navigating the uncertainty of the disease course,[11] and is proposed as a component of patient-centered care in chronic illness. [12] Hope has been identified as an important source of motivation for medication adherence in other chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations